Identifying the greenhouses by Google Earth Engine to promote the reuse of fragmented land in urban fringe. (April 2021) - Yang, Guofu; Xu, Ronghua; Chen, Yi; Wu, Zhaoping; Du, Yuanyuan; Liu, Shun; Qu, Zelong; Guo, Kejian; Peng, Changhui; Chang, Jie; Ge, Ying
Highlights: Greenhouses for cultivation concentrated in urban fringe. The average area of greenhouses increases with the distance from city center. Economic returns of greenhouses in urban fringe are higher than rural area. A strategy for land development and degradation mitigation can be achieved win-win. Abstract: A challenge in urbanization is how to improve the usage of temporary fragmented land, alleviate land degradation and ensure food self-sufficiency. The greenhouses for cultivation have the potential to utilize the fragmented lands, yet there are little known of their spatial information. This study developed a framework to visually identify greenhouses and mapped the spatial pattern through the Google Earth Engine. Based on the investigation of 28, 700 plots in three cities in China, it has found that: (1) the greenhouses distribution peaked at 1−2 km outside the built-up area; (2) more than 60 % of the greenhouses are less than 0.5 ha and the area increase with the distance from city center, which enabled the greenhouses to adapt to the fragmented lands; (3) the economic returns (average 2, 400 yuan ha −1  yr −1 ) were much higher than the environmental impacts related to land degradation (500 yuan ha −1  yr −1 ); and (4) the economic returns provided by the greenhouses near urban fringes were higher than those in the rural, indicating the economic incentives and feasibility of greenhouse cultivation in urban fringes. This study will help decision-makers to form more effective strategies for utilizing temporary fragmented and degraded land to contribute to sustainable development of cities.